Population genomics of Drosophila suzukii reveal longitudinal population structure and signals of migrations in and out of the continental United States. Issue 12 (2nd October 2021) - Lewald, Kyle M; Abrieux, Antoine; Wilson, Derek A; Lee, Yoosook; Conner, William R; Andreazza, Felipe; Beers, Elizabeth H; Burrack, Hannah J; Daane, Kent M; Diepenbrock, Lauren; Drummond, Francis A; Fanning, Philip D; et al.
Abstract: Drosophila suzukii, or spotted-wing drosophila, is now an established pest in many parts of the world, causing significant damage to numerous fruit crop industries. Native to East Asia, D. suzukii infestations started in the United States a decade ago, occupying a wide range of climates. To better understand invasion ecology of this pest, knowledge of past migration events, population structure, and genetic diversity is needed. In this study, we sequenced whole genomes of 237 individual flies collected across the continental United States, as well as several sites in Europe, Brazil, and Asia, to identify and analyze hundreds of thousands of genetic markers. We observed strong population structure between Western and Eastern US populations, but no evidence of any population structure between different latitudes within the continental United States, suggesting that there are no broad-scale adaptations occurring in response to differences in winter climates. We detect admixture from Hawaii to the Western United States and from the Eastern United States to Europe, in agreement with previously identified introduction routes inferred from microsatellite analysis. We also detect potential signals of admixture from the Western United States back to Asia, which could have important implications for shipping and quarantine policies for exported agriculture. We anticipate this large genomic dataset will spur future research into the genomic adaptations underlying D. suzukii pest activity and development of novel control methods for this agricultural pest.